Career Preferences, Leadership Attitudes, and Research Interests among Pharmacy students of Lahore, Pakistan - Zikria Saleem , , Hamid Saeed, Faiza Azhar, Iqra Shafaqat, Soniya Shahzadi, Muhammad Salman , , Furqan K. Hashmi , , Muhammad Azmi Hassali (Journal of Applied Pharmaceutical Science, 2018)
The present study is aimed to evaluate student’s perception about career choices, research interests and leadership attitudes towards pharmacy profession and factors involved in the selection. A cross-sectional survey was conducted at seven different schools of pharmacy in Lahore, Pakistan. The questionnaire used in this study was designed from previous studies conducted in different countries. A total of 720 questionnaires were distributed among the fourth and final year pharmacy students, out of which 562 were returned with the response rate of 78.0%. Majority of the students (30.1%) considered Clinical pharmacist as the best career option and 18.1% students believed that personal interest was the prime reason for the selection of their profession. A large proportion of students (75.6%) believed that leader should take charge of the organization. The participants of the age of 22-23 years were strongly agreed that leader is responsible for controlling the whole group or organization than other age groups (56.0%, p
Keywords: Career choices,Leadership,Pharmacy students,Profession,Research.